Sustainable education: an assessment of carbon footprint at UCSI University and proposed green campus initiative framework / Keoy Kay Hooi and Padzil Hassan - Hooi, Keoy Kay; Hassan, Padzil (Institute of Business Excellence and UPENA, 2010)
As the interest of green business sustainability is generating a lot of interests in the higher education institution, this paper evaluates the implementation of Green Campus Initiative (GCI) at the Unwavering Commitment to Serve Intentionally (UCSI) University Malaysia by evaluating their carbon footprint emission. The carbon footprint calculation and proposed framework presented in this paper aims to encourage other higher Education Institutions in Malaysia to implement the GCI. In order to reduce the environmental impact at UCSI University, the measurement of the CO2 emission was a very important starting point. The paper starts with the literature review about the sustainability and implementation of GCI in other countries outside Malaysia to give an overview regarding the concept. The next section is the calculation of carbon footprint emission of UCSI University with the primary data collected from Logistics and Marketing Department during the year 2008. These primary data were processed with the formulas had been developed earlier and resulted the total carbon footprint produced by UCSI University in one year. Later on, the results of these calculations become the basic concept of developing the proposed framework to be used by higher education institution in Malaysia. Supported by the secondary data (i.e. literature review), a proposed framework of GCI implementation was developed to be tested and empirically validated in future studies. It is hope that result obtained from this paper will provide guidelines for policy maker and management of the universities to acknowledge the importance of GCI to create a sustainable and profitable business application.